An Investigation into Indonesian EFL University Students’ Speaking Anxiety - Abrar, Mukhlash (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2017)
The general purpose of the study was to investigate EFL learners‟ speaking anxiety and its associated factors. More specifically, the study was purposed to examine the constructs of a speaking anxiety and to explore the model for predicting speaking anxiety based on gender, proficiency and class type. Therefore, explanatory factor analysis and multiple linear regression analysis were used. The result indicated that there are two factors in learners‟ speaking anxiety, but they are difficult to name as a result of overlapping variables in each component. With regards to a multiple linear regression test, the finding shows that proficiency variable is the most significant factor for predicting the variation in speaking anxiety.